Development of a Conceptual Model to Understand Disease Burden in Patients With Systemic Lupus Erythematosus and Organ Damage - Lynne Broderick; Wen-Hung Chen; Roger A. Levy; April Mitchell Foster; Cindy Umanzor Figueroa; Kerry Gairy; Deven Chauhan (Journal of Health Economics and Outcomes Research)
**Background:** Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can lead to irreversible organ damage (OD). Data describing the patient burden of OD, as compared with SLE without OD, are limited. **Objective:** To develop a comprehensive conceptual model describing the burden experienced by patients living with SLE-associated OD. **Methods:** There were three phases to this qualitative study. First, a targeted literature review was conducted to inform a draft conceptual model. Second, key opinion leaders (KOLs) were interviewed to assess the draft conceptual model and help shape patient interview materials. Third, patients of different demographic backgrounds from across the United States were interviewed individually to gather their perspectives on living with SLE-associated OD. Data from concept elicitation interviews with KOLs and patients were coded and analyzed using NVivo software to identify the key concepts of the overall patient burden of SLE-associated OD. Findings from the KOL and patient interviews were used to finalize the conceptual model. **Results:** KOLs highlighted that SLE-associated OD carried a higher rate of mortality than SLE alone. Participants with SLE-associated OD (n = 40) experienced detrimental impacts across 4 areas of their lives: physical, cognitive, psychosocial functioning, and economic and work-related well-being. Physical impacts were described by all participants, often affecting their ability to perform everyday tasks. Many also described deterioration of cognitive functioning. Almost all participants experienced emotional impacts and challenges to their relationships and social lives resulting from living with SLE-associated OD. Additionally, SLE-associated OD imposed an economic burden including increased healthcare costs. SLE-associated OD had a more severe and debilitating impact on all aspects of the patient’s quality of life than SLE prior to OD development, including further limitations in activities of daily living after the development of OD. **Discussion:** Study findings guided the development of a comprehensive conceptual model that fully represents the patient experience of living with SLE-associated OD, highlighting the additional burden of OD when compared with SLE alone. **Conclusions:** The conceptual model will inform improvements in disease management, which may result in better patient outcomes and aid development of clinical outcome assessments of disease burden.